Protection of Children as Perpetrators of Criminal Act Stimulated by Pornography Based on Indonesian Laws - Syarif Saddam Rivanie; Avelyn Pingkan Komuna; Alif Arhanda Putra; Putera Fardhi Utama; Abd. Kahar Muzakkir (Faculty of Law, Musamus University, 2021)
This study aims to find out what laws and regulations in Indonesia protect children as criminals due to being stimulated by pornography. This research uses normative legal research methods. The data used in this study are primary data and secondary data. The data analysis technique used is qualitative data analysis techniques. The study results indicate that several laws in Indonesia protect children as perpetrators of criminal act due to being stimulated by pornography. In this case, it consists of Law No. 4 of 1979, Law No. 39 of 1999, Law No. 17 of 2016, Law No. 44 of 2008, and Law No. 11 of 2012. This can be seen from all the considerations of the Panel of Juvenile Judges in deciding the criminal case of sexual intercourse committed by the perpetrator YY against the victim of FH. Therefore, it is hoped that law enforcers regarding the handling of children who commit criminal acts resulting from being stimulated by pornography can distinguish their treatment from criminal acts in general, such as theft. In addition, children who commit crimes due to being stimulated by pornography must also be accompanied by a psychologist to ensure that the child's mental condition can return to normal. Assistance by religious leaders must also be done so that children can return to the right path and be blessed by God.